IMPLEMENTASI PROGRAM SISMANTIK (SISWA PEMANTAU JENTIK) PADA SEKOLAH DASAR SWASTA DALAM UPAYA PENGENDALIAN PENYAKIT DEMAM BERDARAH DANGUE DI DINAS PENDIDIKAN KOTA SEMARANG - Lina Aryanti; Zainal Hidayat (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Student Role in Larva Monitoring (Siswa Pemantau Jentik) is Dangue Hemorrhagic Fever (DHF) control efforts to empower elementary school students to observe the presence of mosquito larvae in the school environment Implementation sismantik program at a private elementary school in Semarang is one of the measures to reduce the death rate of DHF patients in school age children in the city of Semarang. DHF control efforts through monitoring mosquito larvae have been arranged in Semarang City Regional Regulation No. 5 of 2010. The implementation of the monitoring program of mosquito larvae on private elementary school in Semarang in fact still not optimally implemented on all private schools in Semarang it was proven that their school has not been up to implement the program sismantik regularly in private elementary school. Sismantik program conducted in private elementary school in Semarang are still not optimally implemented because there is still a private elementary school that has not routinely perform these government programs.. The purpose of study is to describe the implementation of Student Role in Larva Monitoring (siswa pemantau Jentik) program in private school is controlling dangue disease in Semarang and to identify in habiting factor of Student role in Larva Monitoring program in private school in Semarang. This research is a descriptive study with qualitative approach. The result showed that there are things that inhibit the implementation of the program. This is caused by the weak human resources, communication, characteristic office executive (bereauratic structure). Recommendation that can be given is improving quantity and quality of human resources, improving communications between the policy implementer and making a clear organization structure that can be understood easily.